Effect of psychosocial distress on outcome for head and neck cancer patients undergoing radiation. (17th July 2017) - Chen, Allen M.; Hsu, Sophia; Felix, Care; Garst, Jordan; Yoshizaki, Taeko
Abstract : Objectives/Hypothesis: To determine the impact of pretreatment psychosocial distress on compliance to radiation therapy (RT) and clinical outcomes for patients with head and neck cancer Study Design: Self‐reported responses to the mood and anxiety domains of the University of Washington Quality of Life instrument were reviewed among 133 patients with newly diagnosed head and neck cancer prior to initiating RT. Methods: Varying definitions were used (total number of unexpectedly missed RT days, >5 days continuous interruption of RT outside of weekends, >10 days continuous interruption of RT, and failure to complete prescribed course of RT) to analyze the effect of psychosocial disruption on compliance. Survival was determined using the Kaplan‐Meier method. Results: The prevalence of pretreatment depression and anxiety was 23% and 47%, respectively. Continuous RT breaks >5 days occurred in 46%, 33%, 10%, 9%, and 0% of patients whose mood was rated as "extremely depressed, " "somewhat depressed, " "neither in a good mood or depressed, " "generally good, " and "excellent, " respectively ( P = .0016). The corresponding proportion of patients who did not complete their planned RT was 23%, 11%, 5%, and 3%, and 0%, respectively ( P = .043). The 2‐year overall survival of patients who were "extremely depressed" or "somewhat depressed" at baseline was 71% versus 86% for all others ( P = .026). Depression was independently associated with decreased overall survival on logistical regression analysis. Conclusions: Pretreatment depression predicted for decreased RT compliance and inferior survival for head and neck cancer. Additional research to overcome potential barriers to treatment in this setting may be warranted. Level of Evidence: 4. Laryngoscope, 128:641–645, 2018